ANALISIS KESALAHAN PEMAHAMAN DALAM MATERI SEGIEMPAT MENURUT TINGKAT BERPIKIR VAN HIELE PADA SISWA SMP NEGERI 1 SUPPA KABUPATEN PINRANG - Ashari Nadjib (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2014)
The study aimed at describing students’ miscomprehension in quadrilateral learning material based on Van Hiele’s level of thinking at SMPN 1 Suppa in Pinrang district. The meaning of comprehension in the study was the result of understanding process on Mathematics learning. Test of comprehension was conducted to the two subjects which obtained the data of written test result and interview result. Data were then analyzed with the following steps: (1) data reduction, (2) data presentation, and (3) data verification. The results of the study revealed that (1) the result of grouping test from 25 students, 24 of them were in level 1 (analysis) and 1 student was in level 2 (abstraction), (2) based on the test result of students’ comprehension on quadrilateral lesson material, it was described that the miscomprehension of subject 1 (NF) was due to lack of comprehension concerning parts and attributes of quadrilateral components which created difficulties in discovering the characteristics of each quadrilateral; whereas, the miscomprehension of subject 2 (NA) on quadrilateral lesson material was due to lack of comprehension on the concept and the principles of each of quadrilateral which created difficulties in comprehending the related correlation between each of quadrilateral and difficulties in defining each of quadrilateral.